202: Sibling Superhero Day – Honouring Siblings of Medically Complex Children at the Alberta Children's Hospital. Issue 6 (1st June 2014) - Kwolek, EM; Wilson, K; Hall, S
Abstract: BACKGROUND: Medically complex children are becoming a larger proportion of the inpatient population at pediatric tertiary care centers. With increasingly lengthy stays, the families of these children feel significant effects. Notably, siblings of medically complex and chronically unwell children are often not the primary focus of most families. There is a body of qualitative research that shows regardless of the underlying etiology of pathology, many siblings feel overlooked and demonstrate compromised psychosocial wellbeing. 'Sibling Superhero Day' at the Alberta Children's Hospital was established to recognize and celebrate the siblings of chronically ill children. OBJECTIVES: Review literature surroundings the needs of siblings of medically complex children Review reported outcomes of siblings in a variety of medical environments Describe the execution of Sibling Superhero Day at the Alberta Children's Hospital as a resident advocacy project Review findings of a needs assessment survey completed by parents at the event DESIGN/METHODS: A survey was provided to all families who attended the event. Sample size was limited by the families attending Sibling Superhero Day. RESULTS: 21 families completed the survey – Siblings participating in the event ranged from three mos to 22 years – Families attending the event had between 0 and four siblings - some families did have more than one child they considered "sick" – 19 of 21 (90%) of respondents reported moderate to significant impact on the well sibling – 18 of 21 (86%) felt that their family would benefit from additional programs for siblings while another child is admitted to hospital – 8 of 21 (86%) felt that their family would benefit from additional programs for siblings in the community – None of the respondents are accessing community therapy programs for siblings – All respondents found Sibling Superhero Day "helpful" CONCLUSIONS: Sibling Superhero Day was a great success and many families appreciated the hospital community acknowledging the well siblings in these families. None of the families that participated in the event were accessing any outside resources to provide support to siblings and these families rely on in-hospital programming, though the majority felt their family would benefit from such programs.